2010
DOI: 10.1038/nature08890
|View full text |Cite
|
Sign up to set email alerts
|

Caspase activation precedes and leads to tangles

Abstract: Studies of post-mortem tissue have shown that the location of fibrillar tau deposits, called neurofibrillary tangles (NFT), matches closely with regions of massive neuronal death1,2, severe cytological abnormalities3, and markers of caspase activation and apoptosis4–6, leading to the idea that tangles cause neurodegeneration in Alzheimer’s disease and tau-related frontotemporal dementia. However, using in vivo multiphoton imaging to observe tangles and activation of executioner caspases in living tau transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
436
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 475 publications
(466 citation statements)
references
References 30 publications
25
436
1
4
Order By: Relevance
“…To this end, a fluorescent indicator of caspase activation (FLICA) (27) was applied topically to the cortex of the brain in vivo and imaged with multiphoton microscopy. We found that most oxidized neurons were FLICA positive (39 of 44), suggesting a caspase-dependent programmed cell death in most of the neurons with oxidative stress (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, a fluorescent indicator of caspase activation (FLICA) (27) was applied topically to the cortex of the brain in vivo and imaged with multiphoton microscopy. We found that most oxidized neurons were FLICA positive (39 of 44), suggesting a caspase-dependent programmed cell death in most of the neurons with oxidative stress (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…41 Although there is still considerable support for amyloid being a cause of AD, 42 there is also evidence to indicate that Casp6 can be upstream or parallel to Ab and NFT production: lack of correlation between Ab and memory performance despite a strong correlation with Casp6 and PHF-1 in aged hippocampi, 6 Casp6-dependent Ab production in human CNS primary neuron cultures, 15,16 Casp6-dependent, but Ab-independent, neuritic degeneration in APP-transfected human primary neurons, 14 and caspase activity leading to NFT in mice. 8 Targeting Casp6, in addition to Ab and NFT, may be required to efficiently prevent AD progression. In summary, we have shown that hCasp6 expression in mouse CA1 neurons induces neurodegeneration and memory deficits as observed in aged human individuals.…”
Section: Discussionmentioning
confidence: 99%
“…7 In mouse, caspase activity precedes and leads to the formation of NFT-like aggregation. 8 Casp6 activity is involved in axonal degeneration of mouse PNS neurons via amyloid precursor protein (APP) interaction with death receptor 6 9 and in nerve growth factor (NGF)-deprived dorsal root ganglion neurons. 10 Furthermore, Casp6-dependent axonal degeneration is modulated by NGF deprivation of the axonal compartment.…”
mentioning
confidence: 99%
“…20,21,[31][32][33] Hence, caspase-mediated Tau cleavage is viewed as an early pathological event triggering NFT pathology and δTau as a critical toxic moiety underlying neurodegeneration. 21,31,34,35 However, the data supporting a pathogenic role of δTau are correlative and/or based on aberrant overexpression of Tau and δTau. 34,36,37 Thus, the possibility that cleavage of Tau by caspases represents a negative feedback mechanism aimed to eliminate toxic forms of Tau and/or to generate 'beneficial' Tau fragments must still be considered.…”
Section: Introductionmentioning
confidence: 99%
“…21,31,34,35 However, the data supporting a pathogenic role of δTau are correlative and/or based on aberrant overexpression of Tau and δTau. 34,36,37 Thus, the possibility that cleavage of Tau by caspases represents a negative feedback mechanism aimed to eliminate toxic forms of Tau and/or to generate 'beneficial' Tau fragments must still be considered.…”
Section: Introductionmentioning
confidence: 99%